The Effects of Routine Maintenance and Engineer Competence on Aircraft Readiness in an Indonesian Flight Operator - Juniawan, Singgih; Roysen, Uti; Zainuddin, Zafitri; Daruki, Daruki; Alam, Fachrul (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
Airlines in Indonesia play a crucial role in air transportation activities, connecting communities across different regions. This research aims to identify one of the root causes of flight delays in an Indonesian airline by examining the influence of routine maintenance and engineer competence on aircraft readiness. The theory utilized in this research is Multivariate Statistics, notably the Structural Equation Model - Partial Least Squares (SEM-PLS ) method, employed using questionnaire survey data and internal company data, specifically the annual flight delay data. The research findings show that there is a direct influence of routine maintenance schedule on aircraft readiness by 39.70%; there is a direct influence of spare parts availability on aircraft readiness by 27.60%; there is an indirect influence of routine maintenance schedule and spare parts availability on aircraft availability by 11.30%; and there is an indirect influence of engineer competence and spare parts availability on aircraft availability by 7.30%. The hypothesis stating a significant relationship between engineer competence and aircraft readiness was rejected because, in reality, an engineer's competence would not impact the assistance of adequate equipment and spare parts availability.